Agency Relationship in Budgeting at Inclusion Schools in Gunungkidul District - Risma Wira Bharata; Eko Suwardi; Mimin Nur Aisyah (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study explores the effect of budgetary participation on budgetary slack with organizational culture as an intervening variable in inclusive schools. This study used a survey method by distributing questionnaires consisting of six questions for budgetary slack, five questions budget participation, and 23 questions organizational culture. Used purposive sampling, the study included 100 inclusive school principals and ten education office staff who handled the inclusive school budget. Data were analyzed through a path analysis by using PLS. This study shows that budgetary participation affects organizational culture but has no effect on budgetary slack. Moreover, organizational culture does not mediate the relationship between budget participation and budgetary slack. The Office of Education and Inclusive Schools are suggested to establish better communication and strengthen an organizational culture that can encourage inclusive schools to participate in budgeting to reduce budgetary slack in inclusive education.Keywords: Budget Participation, Budgetary Slack, Organizational CultureHubungan Keagenan dalam Penganggaran pada Sekolah Inklusi di Kabupaten GunungkidulAbstrak: Penelitian ini bertujuan untuk menyelidiki pengaruh partisipasi anggaran terhadap senjangan anggaran dengan budaya organisasi sebagai variabel intervening pada sekolah inklusif. Penelitian ini menggunakan metode survei dengan menyebarkan kuesioner yang terdiri dari 6 pertanyaan untuk senjangan anggaran, 5 pertanyaan partisipasi anggaran, dan 23 pertanyaan budaya organisasi. Sampel menggunakan purposive sampling, yang meliputi 100 kepala sekolah inklusif dan 10 pegawai dinas pendidikan yang menangani anggaran sekolah inklusif. Analisis data menggunakan analisis jalur dengan PLS. Penelitian ini menemukan bahwa partisipasi anggaran berpengaruh terhadap budaya organisasi namun tidak dapat menemukan pengaruh partisipasi anggaran terhadap senjangan anggaran. Penelitian ini tidak membuktikan bahwa budaya organisasi dapat memediasi hubungan antara partisipasi anggaran dan senjangan anggaran. Dinas pendidikan dan sekolah inklusif diharapkan dapat menjalin komunikasi yang lebih baik dan memperkuat budaya organisasi yang dapat mendorong sekolah inklusif untuk berpartisipasi dalam penyusunan anggaran sehingga mengurangi senjangan anggaran dalam pendidikan inklusif.Kata kunci: Partisipasi Anggaran, Senjangan Anggaran, Budaya Organisasi